2022
DOI: 10.1111/1753-6405.13213
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctors’ mental health and coronavirus disease safety concerns

Abstract: Objective: This article aims to assess whether caring for COVID‐19 patients impacted junior doctors’ COVID‐19‐related anxieties, general anxiety and depression, and the relative impact of depression, general anxiety and specific COVID‐19 anxiety on work and social functioning during the COVID‐19 pandemic in 2020. Methods: Recruitment occurred between June and August 2020 in New South Wales, Australia. Demographic information, symptoms of depression (PHQ‐9), generalised anxiety (GAD‐7), and COVID‐19‐related anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To our knowledge, the difference in attitudes between mental and physical health amongst junior doctors has not been previously established in the literature. The well-being of doctors and other health-care workers is currently at the forefront of medicine, particularly in light of the COVID-19 pandemic (Lu et al , 2020; Galbraith et al , 2021; Ike et al , 2021; Bartholomew et al , 2022). This finding has important implications for the training and support of junior doctors in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the difference in attitudes between mental and physical health amongst junior doctors has not been previously established in the literature. The well-being of doctors and other health-care workers is currently at the forefront of medicine, particularly in light of the COVID-19 pandemic (Lu et al , 2020; Galbraith et al , 2021; Ike et al , 2021; Bartholomew et al , 2022). This finding has important implications for the training and support of junior doctors in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, one study showed rates of “minor psychiatric disorder” (depression and anxiety) at 26.8% in national health service (NHS) employees, in contrast to 17.8% in the general population, with doctors particularly at risk (Wall et al , 1997). More recently, the COVID-19 pandemic has been a particular cause for concern regarding the mental health of doctors (Galbraith et al , 2021; Bartholomew et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, persistent and chronic stress at work-caused by things like high demands, little control over one's work, and job insecurity-can raise the risk of depression. This is especially true for people who work in demanding, high-stress jobs or who lose their jobs or become unemployed[41].…”
mentioning
confidence: 99%